Performance of tidal and non-tidal mangrove constructed wetlands in treating maricultural wastewater. (24th March 2022) - Zhang, Tingfeng; Liu, Chaoxiang; Wei, Lili; Tian, Shaohua; Li, Jie; Ndayambaje, Patrick; Huang, Xu; Liu, Lin; Ndagijimana, Pamphile
Abstract: This study aims to evaluate the removal efficiency of nitrogen and phosphorus in the tidal and non-tidal constructed wetlands with typical mangrove ( Aegiceras corniculatum ) as a wetland plant model to treat simulated marine wastewater. The results showed that the average removals of NO2 − -N, NO3 − -N, NH4 + -N, TN and TP were 88.4, 80.5, 81.4, 79.7 and 40.8%, respectively, in the non-tidal subsurface flow (HF) mangrove wetland, and 65.3, 61.3, 90.6, 60.1 and 19.2% in the tidal (TF) mangrove wetland, and 11.4, 64.6, 68.7, 56.6 and 16.3% in the non-tidal free water surface (FWS) mangrove wetland, respectively. Moreover, it was observed that the composition of microbial communities in the HF mangrove wetland was beneficial to the nitrogen cycle and has more quantitative associations of N-metabolism genes. The results indicated that non-tidal HF mangrove wetland has a stable and an effective capacity for potential treatment of marine wastewater compared with the non-tidal FWS mangrove wetland and tidal TF mangrove wetland. HIGHLIGHTS: Mangrove constructed wetlands show the potential ability for marine wastewater pollution control and remediation. Non-tidal HF mangrove wetland is the most efficient for nitrogen and phosphorus removal. Advantages of microbial community structure and N-metabolism genes in HF mangrove wetland are revealed. Graphical Abstract